Flammability Performance of Ethylene-propylene-diene-terpolymer/Polypropylene-Based Thermoplastic Elastomers - Lu, Hongdian; Xie, Jingsong; Ma, Yaqing; He, Hui; Wu, Haotian (Asian Journal of Chemistry, 2013)
The synergistic effect of organically modified montmorillonite on flammability properties and thermal stability of magnesium hydroxide and red phosphorous flame retardant ethylene-propylene-diene-terpolymer/polypropylene thermoplastic elastomers was investigated. The results revealed that organically modified montmorillonite could improve fire safety of thermoplastic elastomer/magnesium hydroxide/red phosphorus [TPE/MH/RP] materials by promoting the formation of compact and integrated chars.